Fine structure analysis of the WT1 gene in sporadic Wilms tumors. - Varanasi, R (1994)
Molecular genetic studies indicate that the etiology of Wilms tumor (WT) is complex, involving at least three loci. Germ-line mutations in the tumor suppressor gene, WT1, have been documented in children with WTs and urogenital developmental anomalies. Sporadic tumors constitute the majority (> 90%) of WT cases and previous molecular analyses of the WT1 gene have focused only on the DNA-binding domain. Using the single-strand conformational polymorphism (SSCP) assay, we analyzed the structural integrity of the entire WT1 gene in 98 sporadic WTs. By PCR-SSCP we find that mutations in the WT1 gene are rare, occurring in only six tumors analyzed. In one sample, two independent intragenic mutations inactivated both WT1 alleles, providing a singular example of two different somatic alterations restricted to the WT1 gene. This case is consistent with the existence of only one tumor suppressor gene at 11p13 involved in the pathogenesis of WTs. Our data, together with the previously ascertained occurrence of large deletions/insertions in WT1, define the frequency at which the WT1 gene is altered in sporadic tumors.